Da Kine Talk From Pidgin to Standard English in Hawaii - Ball Carr, Elizabeth (University of Hawai'i Press, 2018)
Hawaii is without parallel as a crossroads where languages of East and West have met and interacted. The varieties of Eng lish (including nee-pidgin) heard in the Islands today attest to this linguistic and cultural encounter."Da kine talk" is the Island term for the most popular of the colorful dialectal forms- speech that captures the flavor of Hawaii's multiracial community and reflects the successes (and failures) of immigrants from both East and West in learning to communicate in English.As the parade of newcomers arrived in Hawaii, marked changes in the English taught by the missionaries appearedloanwords and intonations from Japan, Portugal, China, Korea, and the Philippines were added to the host of Hawaiian words already in use.Da Kine Talk, Part I, gives a brief history of the early plantation pidgin and presents examples of the speech patterns of nine Island speakers who represent five levels of achievement in spoken English. Spelling, phonetic notation, and a simple method of marking stress and pitch enable the reader to follow the text with the characteristic intonation and emphasis of the speakers.Part II , Vocabulary in a Multilingual Community, offers an up-to-date list of loanwords from the several languages heard in Hawaii which, because they provide additional synonyms for conversation and writing, appeal particularly to speakers of standard English. The colorful loanblend is introduced, a double word put together from two different ianguages, resulting in apt expressions such as political shibai, hulihuli chicken, hanai child, and a host of others. The glossary concentrates on bits of nonstandard speech (blad, mo' betta) and helps to answer the persistent question "Where does that expression come from?"